AN EQUILIBRIUM-THEORY OF POLYTYPISM - Yeomans, J; Price, G (1986)
It is shown that statistical mechanical models with short range competing interactions, the axial Ising models, have equilibrium phase diagrams which mirror many of the features of polytypism. In particular (because of a subtle balance between energy and entropy), phases of arbitrarily long wavelength can result from interactions extending only to second neighbours. Phase diagrams of axial Ising models are described, with interactions up to third neighbours, and their relation to polytypism in silicon carbide, cadmium iodide, the spinelloids and other mineral phases are discussed.-J.M.H.